Single Ir atom anchored in pyrrolic-N4 doped graphene as a promising bifunctional electrocatalyst for the ORR/OER: a computational study - Li, Xinyi; Su, Zhanhua; Zhao, Zhifeng; Cai, Qinghai; Li, Yafei; Zhao, Jingxiang (Journal of colloid and interface science, 2022)
[Display omitted] The development of highly-efficient electrocatalysts with bifunctional catalytic activity for oxygen reduction reaction (ORR) and oxygen evolution reaction. (OER) still remains a great challenge for the large-scale application of renewable energy conversion and storage technologies. Herein, by means of comprehensive density functional theory (DFT) computations, we systematically explored the potential of pyrrolic-N doped graphene (pyrrolic-N4-G) supported various transition metal atoms (TM = Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Ru, Pd, W, Os, Ir, and Pt) as electrocatalysts for the ORR and OER. Our results revealed that these TM/pyrrolic-N4-G candidates exhibit high electrochemical stability due to their positive dissolution potentials. Especially, the Ir/pyrrolic-N4-G can perform as a promising bifunctional electrocatalyst for both ORR and OER with the low overpotentials (ηORR = 0.34 V and ηOER = 0.32 V). Interestingly, multiple-level descriptors, including energy descriptor (ΔGOH* - ΔGO*), (ΔGOH*), structure descriptor (φ), and d-band center (ε) can well rationalize the origin of the high catalytic activity of Ir/pyrrolic-N4-G for the ORR/OER. Our findings not only further enrich the SACs, but also open a new avenue to develop novel 2D materials-based SACs for highly efficient oxygen electrocatalysts.